(untitled) (Biological Sciences - PJSIR, 2002)
Leaf extracts from Azadirachta indica, Nicotiana tabacum and Euca lyptus citriodora were tested for their nematicidal effect on Helicotylenchus indicus, Bitylenchus gojfarti and Pratylenchus thomei and on growth and yield of Pavon-76 and Mehran wheat varieties in microplots. All the amendments significantly reduced the population of the nematodes. Average weight of shoot, root and yield were increased by A. indica treatment. Nicotiana tabacum increased the yield in variety Pavon-76.